Answers

2014-10-05T18:31:49+05:30
(a+b)^2=a^2+ 2ab +b^2
(a-b)^2= a^2 + b^2 -2ab
(a+b)(a-b)=a^2 - b^2
(a+b)^3= a^3 + 3a^2b +3ab^2 + b^3
(a-b)^3= a^3 - 3a^2b + 3ab^2 -b^3
(a+b)^4= a^4 + 4a^3b +6a^2b^2 + 4ab^3 + b^4
(a+b)( a^2 -ab + b^2 )=a^3 + b^3
(a - b)(a^2 + ab + b^2) = a^3 - b^3
(a +b+c)^2=a^2 + b^2 + c^2 +2ab + 2bc +2ca
2 4 2
THANKS FOR THIS
WHAT ABOUT (a+b+c)
I HAVE ADDED IT.
Then what about cube
good.
2014-10-11T19:31:38+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
(a+b)^2=a^2+ 2ab +b^2\\ \\(a-b)^2= a^2 + b^2 -2ab\\ \\(a+b)(a-b)=a^2 - b^2\\ \\(a+b)^3= a^3 + 3a^2b +3ab^2 + b^3\\ \\

(a +b+ c)^2 = a^2 + b^2 + c^2 +2 a b + 2 b c + 2 c a \\

a^3+b^3 = (a+b)( a^2 -ab + b^2 ) \\ \\a^3 - b^3 = (a - b)(a^2 + ab + b^2)\\ \\

(a-b)^3= a^3 - 3a^2b+ 3ab^2-b^3\\ \\

(a +b + c)^3\\ = a^3 + b^3 + c^3 + 6abc +3 a^2b+3ab^2+3a^2c+3ac^2+3bc^2+3b^2c\\ \\

(a+b)^4 = a^4 + 4a^3b +6a^2b^2 + 4ab^3 + b^4\\ \\(a+b)^5=a^5+5a^4b+10a^3b^2+10a^2b^3+5ab^4+b^5

(a^4-b^4)=(a-b)(a+b)(a^2+b^2)\\
0